Influenza and Covid-19 Vaccination in 2023: a descriptive analysis in two Italian Research and Teaching Hospitals. Is the On-Site strategy effective? - Perrone, Pier Mario; Villa, Simone; Raciti, Giuseppina Maria; Clementoni, Laura; Vegro, Valentina; Sovenna, Francesco; Altavilla, Augusto; Tomoiaga, Adriana Monica; Beltrami, Valentina; Bruno, Ilaria; Vaccargiu, Marcello; Astorri, Elisa; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Vaccinations represent an extremely effective tool for the prevention of certain infectious diseases - such as influenza and COVID-19 -, particularly for those categories at risk due to both their frail condition or professional exposure, such as healthcare workers. The aim of this study is to describe the course of the anti-influenza and anti-COVID-19 vaccination campaign at two Research Hospitals in Milan, Italy.Study design. Multicentre, cross-sectional study.Methods. For the 2023-24 vaccination campaign, the two facilities opted for two different approaches. At the Hospital A, two different strategies for vaccinating healthcare workers were implemented: a fixed-site vaccination clinic and two mobile vaccination groups run by Public Health residents of the University of Milan. At the Hospital B, on the other hand, a single fixed-site outpatient clinic run by Public Health residents of the University of Milan was used. On the occasion of the campaign, a survey was also carried out using anonymous online questionnaires to investigate healthcare workers attitudes towards vaccination.Results. A total of 1,937 healthcare workers were vaccinated: 756 were immunized against influenza only, 99 against COVID-19 only, and 1,082 against both. The results show a substantial difference in vaccination adherence among medical and nursing staff compared to other professional categories. In particular, the category with the highest vaccination adhesion turned out to be that of medical doctors with 55.7% adhesion while, on the contrary, the category with the lowest adhesion turned out to be that of auxiliary personnel characterized by 7.4% adhesion. At the same time, the comparison between the two hospital facilities showed a double adherence rate by the staff of Hospital A as regards both the flu vaccine (40.6% and 20.1%) and the anti-COVID-19 vaccine (26.4% and 12.3%). Finally, the survey showed that the attitude towards influenza vaccination is lower among auxiliary staff in terms of both knowledge and vaccination attitude.Conclusions. The results of the study show a vaccination adherence in line with that of previous years, although lower than the values recommended by the principal national and international Organizations. The analysis of the differences between the two facilities and the surveys carried out will allow for the implementation of targeted interventions to increase adherence in future campaigns.